FEPSAC position statement: Mental health disorders in elite athletes and models of service provision. (September 2018) - Moesch, Karin; Kenttä, Göran; Kleinert, Jens; Quignon-Fleuret, Cédric; Cecil, Sarah; Bertollo, Maurizio
Abstract: Mental health disorders (MHD) in elite athletes is a topic that has received increased attention in recent years. The overall aim of this position statement is to enhance awareness of this important topic and to critically discuss optimal service provision for athletes who suffer from MHD. In the first part of the paper a short overview of the research on MHD in elite athletes is provided. Elite athletes seem to have comparable prevalence rates for the most common MHD when compared to non-athletic peers, but there are still many disorders that have not been investigated in athletes. Sport specific situations such as injuries, periods of overtraining and career termination may put athletes at an increased risk of developing MHD. In the second part of the paper, models of service provision for elite athletes suffering from MHD from six European countries are presented, focusing on 1) professional service providers, 2) support systems, 3) diagnostic assessment, 4) clinical treatment, 5) performance during treatment, 6) screening, and 7) education systems. It emerges that competencies, certification issues, and professional boundaries of the involved service providers, as well as the structure of the National Health Care systems differ strongly across European countries, which makes defining a golden standard difficult. In the third part of this paper, the authors provide general recommendations for athletes and coaches, clubs, federations, organizations and scholars that hopefully will inspire stakeholders to optimize their support systems. Highlights: Elite athletes have a similar prevalence rate of MHD as the normal population. There is so far a lack of knowledge on how to support elite athletes with MHD. Service provision for MHD vary greatly across European countries. Recommendations for how to best support elite athlete with MHD are proposed.